Design, synthesis and dopamine D4 receptor binding activities of new N-heteroaromatic 5/6-ring Mannich bases - Linz, Sabine; Müller, Jörg; Hübner, Harald; Gmeiner, Peter; Troschütz, Reinhard (Bioorganic & Medicinal Chemistry, 2009)
A series of phenylpiperazine-methyl-substituted 1H-pyrrolo[2,3-c]pyridine, imidazo[1,2-c]-, pyrrolo[2,3-d]- and pyrrolo[3,2-d]pyrimidines were prepared as selective dopamine D4-ligands. The pyrrolo[2,3-d]pyrimidine derivatives 12d (K = 1,9 nM) and 34d (K = 2,4 nM) as well as the pyrrolo[3,2-d]pyrimidine Mannich base 49f (K = 2,8 nM) showed high dopamine D4 receptor activity superior to the atypical antipsychotic agent clozapine. © 2009 Elsevier Ltd. All rights reserved.